Tensile Properties Evaluation of Paper Pulp Packaging at Different Sections and Orientations on the Egg Tray - AKIAH, MASNI AZIAN; HASOLOAN, HAERY IAN PIETER; YAAKOB, MOHD YUHAZRI (2012)
Paper-based material has been frequently used as part of packaging solution as an option towards reducing municipal solid waste generation. Various studies on mechanical behaviour of paper-pulp packaging material have been conducted based on the machining direction and cross machining direction. However, there is still gap of information on paper-pulp packaging material behaviour at diagonal direction. A study has been conducted to investigate the variability to tensile properties of paper-pulp packaging at various packaging section (draft and base surface) and different specimen orientation (horizontal, vertical, and diagonal direction). In this research, results from the stress-strain relationship obtained from tensile and compression tests are presented. The data obtained are further analysed using ANOVA to find out whether material variations are significantly different with varying sections and orientations. Findings in this research supported the anisotropic properties of paper-based packaging material. Draft surfaces exhibit weaker strength than base surface. Also, the variability of stiffness and strength of specimens are more significant in horizontal and vertical direction compared to diagonal direction.